An educational laboratory virtual instrumentation suite assisted experiment for studying fundamentals of series resistance–inductance–capacitance circuit. (2nd November 2017) - Rana, K.P.S.; Kumar, Vineet; Mendiratta, Jatin
ABSTRACT: One of the most elementary concepts in freshmen Electrical Engineering subject comprises the Resistance–Inductance–Capacitance (RLC) circuit fundamentals, that is, their time and frequency domain responses. For a beginner, generally, it is difficult to understand and appreciate the step and the frequency responses, particularly the resonance. This paper proposes a student-friendly teaching and learning approach by inculcating the multifaceted versatile software LabVIEW TM along with the educational laboratory virtual instrumentation suite hardware, for studying the RLC circuit time and frequency domain responses. The proposed approach has offered an interactive laboratory experiment where students can model circuits in simulation and hardware circuits on prototype board, and then compare their performances. The theoretical simulations and the obtained experimental data are found to be in very close agreement, thereby enhancing the conviction of students. Finally, the proposed methodology was also subjected to the assessment of learning outcomes based on student feedback, and an average score of 8.05 out of 10 with a standard deviation of 0.471 was received, indicating the overall satisfaction of the students.